N-linked glycan structures of the human Fcγ receptors produced in NS0 cells. - Cosgrave, E; Struwe, W; Hayes, J; Harvey, D; Wormald, M; Rudd, P (2013)
Immune recognition of nonself is coordinated through complex mechanisms involving both innate and adaptive responses. Circulating antibodies communicate with effector cells of the innate immune system through surface receptors known as Fcγ receptors (FcγRs). The FcγRs are single-pass transmembrane glycoproteins responsible for regulating innate effector responses toward antigenic material. Although immunoglobulin G (IgG) antibodies bind to a range of receptors, including complement receptors and C-type lectins, we have focused on the Fcγ receptors. A total of five functional FcγRs are broadly classified into three families (FcγRI, FcγRII, and FcγRIII) and together aid in controlling both inflammatory and anti-inflammatory responses of the innate immune system. Due to the continued success of monoclonal antibodies in treating cancer and autoimmune disorders, research is typically directed toward improving the interaction of antibodies with the FcγRs through manipulation of IgG properties such as N-linked glycosylation. Biochemical studies using recombinant forms of the FcγRs are often used to quantitate changes in binding affinity, a key indicator of a likely biological outcome. However, analysis of the FcγRs themselves is imperative as recombinant FcγRs differ greatly from those observed in humans. In particular, the N-linked glycan composition is significantly important due to its function in the IgG-FcγR interaction. Here, we present data for the N-linked glycans present on FcγRs produced in NS0 cells, namely, FcγRIa, FcγRIIa, FcγRIIB, FcγRIIIa, and FcγRIIIb. Importantly, these FcγRs demonstrate typical murine glycosylation in the form of α-galactose epitopes, N-glycolylneuraminic acid, and other key glycan properties that are generally expressed in murine cell lines and therefore are not typically observed in humans.